Model of Metal-Oxide-Semiconductor Contact Characteristics and Carrier Impurity Concentration in Depletion and Oxide Regions - Ngaderman, Hubertus; Sinaga, Ego Srivajawaty (Jurnal Fisika Papua, 2024)
The aim of this research is to obtain characteristic modeling for forward and reverse voltages and the role of oxide as a barrier in the contact between metal semiconductors. When a forward or reverse voltage is applied, both types of  semiconductor exhibit different characteristics. In this study, only these types are considered. The carrier concentration impurity within the semiconductor, width of the oxide material, depletion region, and active region are also reviewed.  The method used was to examine the concept of a metal – oxide – semiconductor contact. In addition, the basic concept of energy bands is used to explain carrier flow events in semiconductors, which present band gaps, conduction band levels, and valence energy levels. The first research result is the characteristics of a metal – oxide – semiconductor-type connection  when a negative and positive voltage  is applied to a metal plate. The second is to find an equation for determining the concentration of substrate impurities. This equation shows the concentration of impurities in the semiconductor and the width of the oxide material, depletion region, and active region.